Refleksi Pembelajaran Aplikasi Medical Writting Presentation pada Mahasiswa Semester Satu Fakultas Kedokteran - Kevin Yulianto; Elisabeth Rukmini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2014)
Background: Medical students need the ability to write and present research. Skills needed are referencing, using internet to help their research, and searching literatures through search engines. The lack of students’ ability about searching a valid and reliable literature in the field of health and medicine according to EBM principle is a profound problem. Reflective thinking is also needed for the students to be able to reach meaningful learning. This study aimed to analyze the students’ reflective writings within the Medical Writing Program. Method: This research was a descriptive-explorative study using a qualitative approach. Subjects comprised 207 first semester medical students of Atma Jaya Catholic University of Indonesia batch 2012. Qualitative data were collected from students’ written reflections about their learning experiences in MWP program. Qualitative analysis utilized content analysis included identification, coding, categorization, and synthesis.Results: Students found that Zotero® was helpful as reference manager program in their writings. Zotero® Volunteer Troops also helped them in learning to use Zotero® and they felt more comfortable learning from their peers. EBM helped students searching and synthetizing literatures. Students also indirectly learned soft skills such as teamwork, time management, and speed reading in English (not their natives language)Conclusion: Students had positive views of the program and its implementation. Students understood the importances of learning the MWP and felt that they could implement their studies directly in their academic careers.